PSVII-42 Mitigating effects of DON-contaminated DDGS on pig performance. (7th December 2018) - Levesque, C; Samuel, R; Woyengo, T; Herrick, K; Thaler, R
Abstract: Deoxynivalenol (DON) contamination of DDGS is a recurring problem. Chemical pretreatment can be used to reduce the effect of DON-contamination in complete feeds. A total of 247 growing pigs (21.5 ± 2.1 kg; n = 6 pens/treatment) were used to evaluate pretreated DON-contaminated DDGS on pig performance. Experimental diets were corn/soybean meal based containing one of 3 DDGS sources [mycotoxin-free (control, 1.0 ppm DON), DON contaminated (donDDGS, 11.6 ppm DON), and pre-treated DON DDGS (trtDDGS, 7.3 ppm DON)] at 30% diet inclusion. Diets met or exceeded nutrient requirements for growing pigs and were fed for 21 d. Data were analyzed as a repeated measure with main effects of period and diet and pen as experimental unit. Pig BW and feed disappearance were measured at d3, 7, 10, 14, and 21. Mean BW of pigs fed donDDGS was lighter ( P = 0.016) than pigs fed control; pigs fed trtDDGS had intermediate BW (31.3 vs 33.0 and 32.1 kg). Weigh period and diet tended to interact ( P = 0.084) on daily gain such that daily gain was not different between weigh periods for control diet-fed pigs and lower in first 3d for donDDGS- and trtDDGS-fed pigs compared to other periods. donDDGS-fed pigs tended ( P = 0.071) to have lower overall intake compared to trtDDGS-fed pigs and control diet-fed pigs. Pretreatment of DDGS reduced the impact of DON contamination in the first week.